Early ART After Cryptococcal Meningitis is Associated With Cerebrospinal Fluid Pleocytosis and Macrophage Activation in a Multisite Randomized Trial - Scriven, James E.; Rhein, Joshua; Hullsiek, Katherine Huppler; Hohenberg, Maximilian von; Linder, Grace; Rolfes, Melissa A.; Williams, Darlisha A.; Taseera, Kabanda; Meya, David B.; Meintjes, Graeme; Boulware, David R. (The Journal of infectious diseases, 2015)
Introduction. Earlier antiretroviral therapy (ART) initiation in cryptococcal meningitis resulted in higher mortality compared with deferred ART initiation (1–2 weeks’ vs 5 weeks postmeningitis diagnosis). We hypothesized this was due to ART-associated immune pathology, without clinically recognized immune reconstitution inflammatory syndrome. Methods. Three macrophage activation markers and 19 cytokines/chemokines were measured from cryopreserved cerebrospinal fluid (CSF) and serum during the Cryptococcal Optimal ART Timing (COAT) trial. Comparisons were made between trial arms (early vs deferred) at 1, 8, 14, and 21 days following meningitis diagnosis. Results. More participants with early ART initiation had CSF white cell count (WCC) ≥5/μL at day 14 (58% vs 40%; P = .047), after a median of 6-days ART. Differences were mainly driven by participants with CSF WCC <5/μL at meningitis diagnosis: 28% (10/36) of such persons in the early ART group had CSF WCC ≥5/μL by day 14, compared with 0% (0/27) in the deferred arm (P = .002). Furthermore, Kampala participants (the largest site) receiving early ART had higher day-14 CSF levels of interleukin-13 (P = .04), sCD14 (P = .04), sCD163 (P = .02), and CCL3/ MIP-1α (P = .02), suggesting increased macrophage/microglial activation. Conclusions. Early ART initiation in cryptococcal meningitis increased CSF cellular infiltrate, macrophage/microglial activation, and T helper 2 responses within the central nervous system. This suggests that increased mortality from early ART in the COAT trial was immunologically mediated
Keywords: AIDS; Cryptococcal meningitis; HIV; Immunology; IRIS; Macrophage; Randomized controlled trial; sCD14; sCD163